New evidence on cognitive and behavioral consumer confusion when choosing me-too snack packages (2015)
A me-too brand is one that imitates the leading brand in a category, expecting consumers to quickly recognize its attributes. Although this is consistent with a categorization process, the me-too brand should not cause consumer confusion. This study evaluates consumer confusion because of: a) the presence of a leading brand next to a me-too brand, and b) the presence of the brand name on the package. This experimental design includes six categories of snacks (chocolate covered cakes, waffle cookies, chocolate chip cookies, crackers, lollipops, and gummy candy), for each of which we estimate three logit models to determine the probability of occurrence of: a) making an unexpected choice; b) consumer awareness; and c) consumer confusion (a and b simultaneously).